Using a Western-Based Survey to Assess Cultural Perspectives of Dene Mothers in Northern Manitoba - Jonk, Luella Bernacki (First Peoples Child & Family Review, 2009)
With increasing numbers of immigrants entering Canada over the past several decades, educators have become more sensitive to the various genres of communication competence and discourse patterns within a given culture. This is especially true for the Aboriginal students struggling to acclimate into Western curricula. The purpose of this study was to explore Aboriginal mothers’ perspectives on language acquisition for their children. Thirty Dene speaking mothers from a northern first nation community were administered a survey in a face to face format. The survey was replicated in part from previous studies on language acquisition of cultural groups in Canada. This paper will describe the challenges in trying to adapt such a survey, including issues of administration, translation, and survey validity and reliability. Challenges in adhering to Western research standards while displaying cultural sensitivity to its participants by way of acknowledging the community’s indigenous knowledge and English as an alternative language (EAL) issues are discussed.